Synthesis, crystal structure, Hirshfeld surface analysis, and DFT studies on (2,2’-bipyridine)chlorobis(N,N-bis(thiophen-2-ylmethyl)dithiocarbamato-S,S’)zinc(II) complex - Eswari, Soundararajan; Thirumaran, Subbiah (European Journal of Chemistry, 2022)
Bis(N,N-bis(thiophen-2-ylmethyl)dithiocarbamato-S,S’)zinc(II) complex (1) and (2,2’-bipyridine)chlorobis(N,N-bis(thiophen-2-ylmethyl)dithiocarbamato-S,S’)zinc(II) complex (2) were synthesized. Complex 2 (final product) was structurally characterized by single crystal X-ray diffraction studies. Complex 2 (C21H18ClN3S4Zn) crystallized in triclinic crystal system with space group P-1 (no. 2), a = 8.7603(4) Å, b = 10.7488(6) Å, c = 13.0262(7) Å, α = 103.965(2)°, β = 91.913(2)°, γ = 104.944(2)°, V = 1144.07(10) Å3, Z = 2, T = 302(2) K, μ(MoKα) = 1.569 mm-1, Dcalc = 1.572 g/cm3, 14892 reflections measured (4.838° ≤ 2Θ ≤ 56.52°), 5570 unique (Rint = 0.0188, Rsigma = 0.0230) which were used in all calculations. The final R1 was 0.0810 (I > 2σ(I)) and wR2 was 0.2788 (all data). Complex 2 displays distorted square pyramidal coordination geometry. Crystal structure analysis of complex 2 shows that the crystal packing is mainly stabilized by C-H···π (chelate) and C-H···Cl interactions. Hirshfeld surface analysis was carried out to explore deeply into the nature and type of non-covalent interactions. The molecular and electronic structures of complexes 1 and 2 were also studied by DFT quantum chemical calculations.